Synthesis and optical property of one-dimensional spinel ZnMn2O4 nanorods - Zhang, P.; Li, X.; Zhao, Q.; Liu, Shaomin (Springer New York, 2011)
Spinel zinc manganese oxide (ZnMn2O4) nanorods were successfully prepared using the previously synthesized α-MnO2 nanorods by a hydrothermal method as template. The nanorods were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, UV-Vis absorption, X-ray photoelectron spectroscopy, surface photovoltage spectroscopy, and Fourier transform infrared spectroscopy. The ZnMn2O4 nanorods in well-formed crystallinity and phase purity appeared with the width in 50-100 nm and the length in 1.5-2 μm. They exhibited strong absorption below 500 nm with the threshold edges around 700 nm. A significant photovoltage response in the region below 400 nm could be observed for the nanorods calcined at 650 and 800°C.